2007
DOI: 10.1051/0004-6361:20066762
|View full text |Cite
|
Sign up to set email alerts
|

IGR J18483-0311: an accreting X-ray pulsar observed by INTEGRAL

Abstract: Context. IGR J18483−0311 is a poorly known transient hard X-ray source discovered by INTEGRAL during observations of the Galactic Center region performed between 23-28 April 2003. Aims. To detect new outbursts from IGR J18483−0311 using INTEGRAL and archival Swift XRT observations and finally to characterize the nature of this source using the optical/near−infrared (NIR) information available through catalogue searches. Methods. We performed an analysis of light curves and spectra of INTEGRAL and archival Swif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
156
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(174 citation statements)
references
References 29 publications
15
156
3
Order By: Relevance
“…This is naturally provided by a second wind component crossing the neutron star orbit. We note that periodicities in the outburst recurrence begin to be found also in other SFXTs: IGR J18483-0311 displays a recurrence periodicity of ∼18.5 days (Sguera et al, 2007b); this source was at first classified as a Be X-ray transient, but very recently optically identified the companion as a blue supergiant, thus the source is actually a SFXT; IGR J08408-4503 displays an X-ray activity (multiple flare duration and Xray outburst recurrence) which is compatible with an orbital period of 35 days (see Romano et al 2009 for details).…”
Section: Outbursts From Anisotropic Winds: a Preferential Plane For Tsupporting
confidence: 62%
See 1 more Smart Citation
“…This is naturally provided by a second wind component crossing the neutron star orbit. We note that periodicities in the outburst recurrence begin to be found also in other SFXTs: IGR J18483-0311 displays a recurrence periodicity of ∼18.5 days (Sguera et al, 2007b); this source was at first classified as a Be X-ray transient, but very recently optically identified the companion as a blue supergiant, thus the source is actually a SFXT; IGR J08408-4503 displays an X-ray activity (multiple flare duration and Xray outburst recurrence) which is compatible with an orbital period of 35 days (see Romano et al 2009 for details).…”
Section: Outbursts From Anisotropic Winds: a Preferential Plane For Tsupporting
confidence: 62%
“…This property seems to be in contrast with the hypothesis suggested by Bozzo et al (2008) that SFXTs are magnetars. Moreover, Bozzo et al (2008) suggest that, to get the large dynamic ranges observed in SFXTs, these transients should host neutron stars with long spin periods (of the order of 1000 s or larger), which is not observed in SFXTs, to date: indeed, four SFXTs are X-ray pulsars with much shorter spin periods: IGR J11215-5952 (187 s, Swank et al 2007), AX J1841.0-0536 (4.7 s, Bamba et al 2001), IGR J18483-0311 (21 s, Sguera et al 2007b), IGR J16465-4507 (228 s, Lutovinov et al 2005). The large dynamic range between the quiescence and the maximum luminosity at the peak of the flares can, in any case, be explained already if the supergiant winds are clumpy with density contrasts as large as 10 5 (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…INTEGRAL data also showed that IGR J18483-0311 sporadically displays a few days-long X-ray active states (∼3 days), during which fast flares with typical timescales of a few hours can be observed (Krimm et al, 2011;Romano et al, 2010b;Ducci et al, 2013a). Pulsations with a period of ∼21 s were first reported by Sguera et al (2007). Giunta et al (2009) discussed the possible detection of pulsations during the low X-ray intensity states of the source.…”
Section: Discussionmentioning
confidence: 96%
“…Several approaches using X-ray data analysis have shown their effectiveness in identifying the nature of some of these new INTEGRAL sources, such as X-ray timing (e.g., Walter et al 2006;Sguera et al 2007;Del Santo et al 2007;La Parola et al 2010) or spectroscopy and imaging (see for instance Rodriguez et al 2010;Malizia et al 2010;Tomsick et al 2012, and references therein). A&A 556, A120 (2013) Alternatively and also effectively, cross-correlation with soft X-ray catalogues and consequent optical spectroscopy on thereby selected candidates allows the determination of the nature and the main multiwavelength characteristics of unidentified or poorly studied hard X-ray objects.…”
Section: Introductionmentioning
confidence: 99%